Development of an air-knife system for highly reproducible fabrication of polydimethylsiloxane microstencils. (22nd July 2015) - Choi, Jin Ho; Kim, Gyu Man
Abstract: In this study, an air-knife system was developed for the automated fabrication of polymer microstencils with microscale perforated patterns. Blowing compressed N2 gas through the air knife provided a uniform laminar gas flow of high intensity suitable for perforating holes in the stencil. The polydimethylsiloxane (PDMS) stencil was replicated from a master mold prepared by photolithography. When the prepolymer of PDMS was spin-coated onto the master mold, a thin layer of the prepolymer remained on top of the master's structure and consequently prevented the formation of the perforated patterns. This residual layer was easily removed by the presented air knife. The air-knife system controlled the flow rate of N2 gas and the conveying speed of the master mold; therefore, the system possessed high reproducibility compared to manual gas blowing. Its use reduced the fabrication time for perforated biocompatible polymer microstencils, allowing for their mass production via an automated system. The validity of this suggested method was proven through experiments and was evaluated by application in various fields.